2017
DOI: 10.1101/117150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

powsimR: Power analysis for bulk and single cell RNA-seq experiments

Abstract: Power analysis is essential to optimize the design of RNA-seq experiments and to assess and compare the power to detect differentially expressed genes in RNA-seq data. PowsimR is a flexible tool to simulate and evaluate differential expression from bulk and especially single-cell RNA-seq data making it suitable for a priori and posterior power analyses.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 18 publications
(11 reference statements)
0
52
0
Order By: Relevance
“…MAST uses a hurdle model to account for dropout while modelling changes in gene expression dependent upon condition and technical covariates. It was the best‐performing single‐cell DE testing method in the aforementioned study (Soneson & Robinson, ), and outperformed bulk and single‐cell methods in a small‐scale comparison on a single dataset (Vieth et al , ). While MAST has a 10‐fold to 100‐fold faster runtime than weighted bulk methods (Van den Berge et al , ), a further 10‐fold speedup can be achieved using limma–voom (Law et al , ).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…MAST uses a hurdle model to account for dropout while modelling changes in gene expression dependent upon condition and technical covariates. It was the best‐performing single‐cell DE testing method in the aforementioned study (Soneson & Robinson, ), and outperformed bulk and single‐cell methods in a small‐scale comparison on a single dataset (Vieth et al , ). While MAST has a 10‐fold to 100‐fold faster runtime than weighted bulk methods (Van den Berge et al , ), a further 10‐fold speedup can be achieved using limma–voom (Law et al , ).…”
Section: Introductionmentioning
confidence: 94%
“…We cannot expect that a single normalization method is appropriate for all types of scRNA-seq data. For example, Vieth et al (2017) showed that read and count data are best fit by different models. Indeed Cole et al (2019) find that different normalization methods perform optimally for different datasets and argue that their scone tool should be used to select the appropriate normalization method for a specific dataset.…”
Section: Normalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…More packages are now including their simulation functions and some tools have been developed for the specific purpose of generating realistic synthetic scRNA-seq datasets (powsimR 31 , Splatter 32 ). Classification of cells into known groups has also 20, 2017; increased as reference datasets become available and more tools are identifying or making use of co-regulated gene networks.…”
Section: Figure 3 (A) Categories Of Tools In the Scrna-tools Databasementioning
confidence: 99%
“…Furthermore, for typical univariate supervised inference problems such as regression, tools for power analysis exist to assess what parameter values in models can be reliably inferred from data of varying sizes [2,3]. However, questions of interest in single-cell RNA-seq analysis do not have a structure where performance can be directly quantified and appropriate subsampling and quantification of per- Figure 1) Outline of the workflow for subsampling reads and cells, fitting models with a variational autoencoder, evaluating validation error, and visualization.…”
Section: Introductionmentioning
confidence: 99%